AN ANALYSIS OF DIRECTIVE SPEECH ACTS BY SEARLE THEORY IN “SLEEPING BEAUTY” MOVIE SCRIPT - Fara Della; Barnabas Sembiring (Universitas Bengkulu, 2018)
This research aims to find out the types of Directive Speech Acts by the characters in “Sleeping Beauty” movie script based on the theory that proposed by Searle theory and analyze the types of directive speech acts that most frequently used in the movie script and the possible reason for it. The subject of the research was the script of the conversation between the characters. The type of this research is Descriptive Quantitative research. In this research, the researcher used documentation as the instrument. The object of this study is the “Sleeping Beauty” movie script by Casper Van Dien. The results of the research show that, first, the types of directive speech acts were Command, request, permission, prohibition, and question. Second, the types of directive speech act that most frequently used were command type. In terms of types, the command is in the highest rank (51 utterances) and prohibition ( 2 utterances)) is in the lowest rank. In terms of reason, the command types (51 utterances) is the most frequently used, because it usually shows the strength of each character very clearly. And also the movie genre also influences the use of its directive speech acts itself.